Factores de competitividad que influyen en el desarrollo exportador de las micro y pequeñas empresas del sector textil de la provincia de Trujillo - 2017 - Kurokawa Guevara, Augusto Sadayoshi (2018)
The textile industry has become one of the main generators of employment and foreign exchange in Latin America. This region has positioned itself as the second largest international supplier of clothing to the United States. The textile sector in many countries became a key to diversify the export sector, which in the eighties focused almost entirely on traditional agricultural products. The key to insert a small textile business in national and global chains value in a sustainable way is to make them competitive. This means being able to offer the buyer the quantity and quality of a specific product more efficiently, in terms of costs and timeto other suppliers of the same product. This implies the need for continuous improvements in both productivity and product quality in order to satisfy the requirements of buyers. These improvements also relate to improving logistics, -rentable and ready to be sent to the market- and of course, achieve economies of scale packaging. This paper aims competitiveness factors that positively or negatively affect the development of textile exporter micro La Libertad.